A commentary on Stesichorus - Davies, M (1979)
﻿An abstract of a commentary - which must follow the winds and turns of the text it explains - cannot reasonably be expected. The present opportunity may, however, be used to summarise the principles behind my own specimen. Any commentary tries (at least in theory) to examine its subject's work from as many viewpoints - historical, philological, etc. - as are appropriate and possible. When the works, like Stesichorus', only exist in a highly fragmentary state, this impossible ideal seems slightly more capable of fulfilment than usual: there is less text and so more time (and space) to explain it. This approach from a large number of different viewpoints is not only more attainable in Stesichorus' case, it is more necessary: isolated scraps of poetry, whose context is often totally uncertain, require full examination before their secrets can be yielded up. Hence, for instance, the amount of effort devoted by other scholars - and now by me - to the subject of Stesichorus and art. And hence the exceedingly detailed scope of the commentary. For evern one word fragments have a philological and, sometimes, a stylistic value. And the speculation of earlier critics must be evaluated and preserved if plausible, or candidly denounced if unlikely, in an attempt to prevent repetition of the error.